2008
DOI: 10.1007/s10722-008-9353-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of watermelon (Citrullus lanatus) accessions collected from Turkey for morphological traits

Abstract: In this study, the Turkish watermelon genetic resources were collected in 2004 and morphologically characterized in 2005. The collection comprising of traditional cultivars and local accessions were collected from 15 different provinces of Southeastern Anatolia, Aegean, Marmara-Thrace, Middle Anatolia and Mediterranean regions of Turkey where local watermelon types are widely grown. A total of 134 accessions were characterized morphologically according to UPOV descriptor list for 56 qualitative characters (6 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 16 publications
5
26
0
Order By: Relevance
“…The utilization of imported seeds of narrow genetic basis by the producers may endanger the existing variability. The same situation is being reported for cucurbits species, such as the watermelon germplasm in Turkey, where modern varieties are replacing local varieties due to the need of increasing profits, leading to a worry about the extinction of these genetic resources (Solmaz and Sart 2009). Also, the same concern was verified related to Lagenaria siceraria by Yetisir et al (2008), which verified a decrease on the variability found in this another cucurbit species.…”
Section: Introductionsupporting
confidence: 59%
“…The utilization of imported seeds of narrow genetic basis by the producers may endanger the existing variability. The same situation is being reported for cucurbits species, such as the watermelon germplasm in Turkey, where modern varieties are replacing local varieties due to the need of increasing profits, leading to a worry about the extinction of these genetic resources (Solmaz and Sart 2009). Also, the same concern was verified related to Lagenaria siceraria by Yetisir et al (2008), which verified a decrease on the variability found in this another cucurbit species.…”
Section: Introductionsupporting
confidence: 59%
“…As well as its' location, overlapping the Near Eastern and Mediteraanean Vavilovian centres of plant diversity makes Turkey significant in terms of plant genetic resources (Küçük et al 2002). However, some are not available at the moment, Turkey possesses precious watermelon landraces in different ecological regions (Solmaz and Sari 2009). Genetic resources are valuable reservoirs of potentially useful genes and can be beneficial in breeding studies for the future needs.…”
Section: Introductionmentioning
confidence: 99%
“…Although Turkey is not the origin of watermelon, a wide range of diversity has been observed among Turkish genetic resources (Huh et al 2008;Solmaz and Sari 2009).…”
Section: Introductionmentioning
confidence: 99%